EVALUASI PROGRAM EKSTRAKURIKULER WAJIB PRAMUKA PADA KURIKULUM 2013 DI SMA NEGERI 1 PEKANBARU - Ida Nila; Isjoni Isjoni; Murni Baheram (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2020)
This research is a qualitative research that aims to evaluate the scout extracurricular program in the 2013 curriculum in SMA Negeri 1 Pekanbaru. This study focuses on the evaluation of mandatory extracurricular program in the curriculum of 2013 in SMA Negeri 1 Pekanbaru with aspects observed as subfokus of this research problem to support the focus of research is 1) Evaluation of extracurricular context of scout in SMA Negeri 1 Pekanbaru, 2) Evaluation Inputekstrakurikuler mandatory scout in SMA Negeri 1 Pekanbaru, 3) Evaluation The process of extracurricular implementation of compulsory scout in SMA Negeri 1 Pekanbaru. The data collection of this research is done by observation, interview, and documentation with Evaluation Models (Substantive) model approach, that is the evaluation model of goal achievement. The results of this research in terms of implementation of context evaluation in extracurricular activities must be good scout. Looks good because it is based on Permendikbud Number 63 Year 2014 About Scouting Education, the implementation of this scout extracurricular is to include teachers in training and get MD certificates to be a supervisor on the extracurricular must scouts. Invite resource persons to increase knowledge of Scout Coaches. Preparing facilities and infrastructure periodically to support scout activities. Evaluation of inputs where for extracurricular activities is mandatory scout in SMA Negeri 1 Pekanbaru students' ability about scout is very minimal because of the number of students from various junior high schools that have not used the Curriculum 2013 and do not place the scout as a compulsory extracurricular. Results of Evaluation Process Implementation of scout activities in SMA Negeri 1 Pekanbaru for planning is made by involving principals, student representatives, scout coodinator and scout coach. This planning is made for 1 year where the beginning of its implementation in the new school year. Types of activities undertaken in this scout activities are social work, ceremonial education, scouting skills, UN and monitored directly by the supervisor of the Education Office Pekanbaru City.